Impact of Training in Sports Games and Cyclic Sports Events on Cardiovascular System, Motor and Sensomotor Abilities of 11-14 Year-Old Boys - Arūnas Emeljanovas; Jonas Poderys; Eurelija Venskaitytė (Lithuanian Sports University, 2018)
Individual development depends not only on inherent qualities but also on the effective influence of the environment. The aim of this study was to compare the effect of variable intensity as partially regulated physical loads which are appropriate for sports games performances and cyclic nature as strictly regulated physical loads which is appropriate for cyclic sports events on the dynamics of muscular, cardiovascular and central nervous system (CNS). The contingent of this study was 70 boys of 11-14 years of age: cyclic sports events (track and field athletes) and sports games athletes (basketball, volleyball, football players) were tested for four years. The following methods were used: Tapping test, Roufier exercise test, vertical jump test, 30 s maximal jumping test, measurements of ABP, electrocardiography, dynamometry, measurements of the body mass components. Sports games athletes were superior over cyclic sports events athletes taking into account CNS mobility, anaerobic efficiency and anaerobic work capacity. Evaluating boys' motor abilities (performing vertical jump and 30 s maximal jumping test), it was observed that these indices were improving with age in both sports games athletes and cyclic sports events athletes groups, but they did not vary statistically significantly among each other. Evaluating the indices of muscle power by dynamometry measurements, it was determined that cyclic sports events had greater influence on muscle power. These results show that 11-14 year-old boys are still developing and are not mature. Long-time research of body components revealed that body fat decreased with age and active body mass and total body liquid mass increased with age, but in case of sports games athletes and cyclic sports events athletes, they did not vary. Sports games athletes were characterized as having lower HR values than cyclic sports events athletes, though during all investigation statistically significant differences were observed in 13 year-old group. Statistically significant differences were found evaluating JT interval data. The development rate of muscular, cardiovascular system and performance abilities of CNS increase under the influence of variable intensity of physical load which is appropriate for sports games in contrast to cyclic sports events, which is an essential external factor at the age of 11-13. Decisive influence of endogenous factors on growth and development of boys significantly increases at the age of 13-14 years due to the changes of cardiovascular system, and CNS indices accelerate. Keywords: cardiovascular system, central nervous system, cyclic sports, sports games.